Majątki ziemiańskie okolic Urzędowa na przełomie XIX i XX w. a proces uprzemysłowienia - Wnuk, Anna (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2010)
Industrialization of rural Polish lands, especially in Lublin and Urzędów region, was lagging behind comparing with the changes which were taken place in Western European countries. Landlords education (such as Institute of Agriculture and Forestry in Marymont near Warsaw, Farm and Forestry Institute in Puławy), reading and travelling to other countries made them to revise their methods of farm management. The landlords of Urzędów region, such as Gosiewski from Radlin, Nowakowski from Ratoszyn, Piasecki from Popkowice, Zembrzuski from Moniaki, Kochanowski from Łopiennik, Mazurkiewicz and Węgliński from Ostrów as well as Hempel from Skorczyce, were motivated by the new methods of rural management and people care. The lack of capital, poor development of road and railway network, the First World War damage caused some difficulties in rural industrialization process. The types of cultivation grown were matched by the estate owners to the raw material resources required in agro-food industry. Industrial plants, especially beetroots, potatoes, barley, hops started to be grown in giant farms (folwarks). They provided the needed mainstay of raw material for the sugar factory, distillery, breweries and starch factory. The interesting example of a modern landlord was Jan Kleniewski from Kluczkowice, who faced up to the challenges of that time. His achievement was the development of agro-food industry: distillery, breweries, sawmill, turpentine factory, parquet factory, shingle factory, tile factory, wickerwork factory, sugar factory. The next industrially advanced farm belonged to the family of Piasecki from Popkowice, where starch factory, brewery, sawmill, brick yard and windmill were established. Unfortunately, the development of other farms in Urzędów region was worse. Some of them had only such industrial facilities as windmills, distilleries and sawmills.The landlords had their own ideas concerning the rural industrialization in the country. Leon Hempel from Skorczyce raised an issue of a rural small scale industry. The activity of landlords community representatives from Urzędów region in the field of industrialization shows the changing of their points of view, which concerns not only the modern methods of farming in rural regions but also their industrial development as well.